Let's Go for a Drive! - Willems, Mo (New York, 2012)
Elephant Gerald and Piggie want to go for a drive, but as Gerald thinks of one thing after another that they will have to take along, they come to realize that they lack the most important thing of all.
"An Elephant and Piggie book."
Keywords: Fiction; Pigs; Fiction; Elephants; Automobile travel; Fiction; Humorous fiction